Anthrax revisited: how assessing the unpredictable can improve biosecurity - Sabra, Dunja Manal; Krin, Anna; Romeral, Ana Belén; Frieß, Johannes Ludwig; Jeremias, Gunnar (Frontiers in Bioengineering and Biotechnology, 2023)
B. anthracis is one of the most often weaponized pathogens. States had it in their bioweapons programs and criminals and terrorists have used or attempted to use it. This study is motivated by the narrative that emerging and developing technologies today contribute to the amplification of danger through greater easiness, accessibility and affordability of steps in the making of an anthrax weapon. As states would have way better preconditions if they would decide for an offensive bioweapons program, we focus on bioterrorism. This paper analyzes and assesses the possible bioterrorism threat arising from advances in synthetic biology, genome editing, information availability, and other emerging, and converging sciences and enabling technologies. Methodologically we apply foresight methods to encourage the analysis of contemporary technological advances. We have developed a conceptual six-step foresight science framework approach. It represents a synthesis of various foresight methodologies including literature review, elements of horizon scanning, trend impact analysis, red team exercise, and free flow open-ended discussions. Our results show a significant shift in the threat landscape. Increasing affordability, widespread distribution, efficiency, as well as ease of use of DNA synthesis, and rapid advances in genome-editing and synthetic genomic technologies lead to an ever-growing number and types of actors who could potentially weaponize B. anthracis. Understanding the current and future capabilities of these technologies and their potential for misuse critically shapes the current and future threat landscape and underlines the necessary adaptation of biosecurity measures in the spheres of multi-level political decision making and in the science community.